Pendidikan Umum, Nilai, dan Karakter dalam Bingkai Pilar Pembangunan Berkelanjutan di Indonesia - Agung Dwi Putra; Dasim Budimansyah; Encep Syarief Nurdin; Rita Milyartini; Lanang Riyadi; Maksud Khoshimov (Fakultas Tarbiyah dan Ilmu Keguruan UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2025)
The Sustainable Development Goals (SDGs) have become a global agenda emphasizing the balance among the social, economic, and environmental pillars, with the governance pillar serving as a reinforcing element. This article aims to critically and comprehensively review the contribution of general education in the internalization of values and character formation as the social pillar of sustainable development. The method employed is a systematic literature review of various academic sources and relevant documents. The review findings indicate that quality education integrating values and character not only supports the achievement of education Goals (SDG 4) but also plays a strategic role in building an inclusive, just, and environmentally conscious society. General education that instills character traits such as mindfulness, curiosity, courage, resilience, ethics, and leadership serves as a crucial foundation in addressing global challenges and strengthening the social pillar of sustainable development. This review implies the need for the development of holistic and contextual curricula and teaching methods to realize a sustainable and just future in Indonesia. Thus, character education within general education can become a strategic instrument in supporting the success of sustainable development.